Phytochemical, Antioxidant and Photo-Protective Activity Study of Bunga Kantan (Etlingera elatior) Essential Oil - Poh-Yen Khor, Fatin Shuhada Na&#;im Mohamed, Ikrimah Ramli, Nur Fatihah Asyiqin Mohd Nor, Siti Khatijah Che Mohd Razali, Jasreen Ariesha Zainuddin, Nur Sahira Mohd Jaafar (Journal of Applied Pharmaceutical Science, 2017)
The three main objectives of this study were to evaluate the extracted essential oil in terms of total phenolic and flavonoids contents, radical scavenging activity and sun protection factor. The antioxidant activity of the essential oil was determined by using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity while the content of total phenol was determined by using Folin-Ciocalteu reagent. Aluminium chloride colorimetric method was used for flavonoid content determination while photo-protective potential was determined by using Mansur’s sun protection factor (SPF) value. The extracted essential oil was found to contain low levels of total phenolic contents (2.30±0.003µg/g as garlic acid equivalent) and total flavonoid contents (254.99±0.64 µg/g as quercetin equivalent) respectively. DPPH free radical scavenging activity of the essential oil was40.73%±1.32 at 200µg/ml. The Mansur’s equation of sun protective factor showed that the essential oil possesses some sun protective potentials. This study suggests that the essential oil from Etlingera elatior could be potentially used as a new source of natural antioxidant and ingredient that can be incorporated into the sunscreen cosmetic products.
Keywords: Essential Oil, Bunga Kantan, Etlingera elatior, Antioxidant, Photo-Protective Activity, Phytochemical.